Stimulus-induced periodic discharges in response to low-frequency photostimulation in a female patient in recovery period after middle cerebral artery stroke - D. S. Kanshina; I. V. Okuneva; M. A. Surma; O. Yu. Bronov; S. S. Nikitin (Эпилепсия и пароксизмальные состояния)
Stimulus-induced rhythmic, periodic, or ictal discharges (SIRPIDs) represent a relatively common phenomenon recorded during a long-term electroencephalogram (EEG) monitoring allowing to capture the altered state and response to auditory, tactile or nociceptive stimulation in critically ill patients. It is a nosologically non-specific phenomenon, and its relation to ictal event remains debated. We present a clinical case in which SIRPIDs were recorded in the affected dominant hemisphere in response to low-frequency photostimulation in a 60-years-old woman recovering after middle cerebral artery stroke. No ictal events were recorded during routine EEG monitoring; the patient was not in critical condition.